FRI0027 Tnf expression on microparticles from rheumatoid arthritis patients mediates endothelial cell fate in vitro. (15th June 2017) - Barbati, C; Vomero, M; Colasanti, T; Novelli, L; Spinelli, FR; Miranda, F; Ceccarelli, F; Finucci, A; Perricone, C; Scrivo, R; Conti, F; Valesini, G; et al.
Abstract : Background: Microparticles (MPs) are small membrane vesicles released by many cell types under physiological conditions or pathological situations. Increased levels of MPs have been reported in patients with autoimmune diseases, such as Rheumatoid Arthritis (RA) (1) which is characterized by an accelerated atherosclerosis. TNF, a key cytokine involved in the pathogenesis of RA, has been associated to RA atherosclerosis (2). Moreover, MPs could also have a role in endothelial dysfunction contributing to atherosclerosis in RA patients. Objectives: The aim of this study was: 1) to evaluate TNF expression on RA-MPs. 2) to estimate the effects of serum RA-MPs on endothelial apoptosis and autophagy before and after in vivo and in vitro treatment with Etanercept. Methods: 15 RA patients were recruited from the Department of Rheumatology Sapienza University of Rome at baseline (T0) and after three months of therapy (T3) with Etanercept. A fasting blood sample was collected and centrifuged two times to obtain platelet-poor plasma rich in MPs. The resulting plasma was stained with Ab anti-TNF and analized by flow cytometry. In vitro effects of serum RA-MPs on endothelium were evaluated using human umbilical vein cell line EA.hy926 . Cells were treated with RA-MPs purified at T0 and T3 and with RA-MPs in vitro treated with Etanercept. At the end of experiments apoptosis and autophagy were evaluated. Apoptosis was analyzed by flow cytometry using a FITC-conjugated annexin V and propidium iodide apoptosis detection kit; autophagy was analyzed by western blot for the expression level of the autophagic marker LC3-II. Results: Our results showed that MPs purified from RA patients at T0 expressed TNF on their surface and this expression decreased after three months of treatment with Etanercept ( p= 0.04). Moreover, serum RA-MPs at T0 significantly increased, in a dose-dependent manner, both apoptosis and autophagy levels in the human umbilical vein cell line EA . hy926 ( p =0.005 and p =0.02, respectively versus untreated cells). After three months of treatment with Etanercept, RA-MPs were not able to significantly change these parameters.Finally, in vitro studies showed that RA-MPs treated with Etanercept significantly decreased surface expression of TNF and were no longer able to modulate apoptosis and autophagy in EA.hy926 cells. Conclusions: Our data demonstrate that serum RA-MPs express TNF on their surface. Moreover, both in vivo and in vitro treatment with Etanercept interfere with the ability of MPs to significantly modulate apoptosis and autophagy of endothelial cells by decreasing surface expression of TNF. References: Beyer C and Pisetsky DS.The role of microparticles in the pathogenesis of rheumatic diseases. Nat. Rev. Rheumatol. 2010;6:21–9. Feldmann M, Brennan FM, Foxwell BM and Maini RN.The role of TNF alpha and IL-1 in rheumatoid arthritis Curr. Dir. Autoimmun. 2001;3:188–99. Disclosure of Interest: None declared